High prevalence of burnout syndrome in Czech general practitioners: A cross-sectional survey - Štěpánek, Ladislav; Patel, Mihir Sanjay; Horáková, Dagmar; Juríčková, Lubica; Býma, Svatopluk (Preventive medicine reports, 2023)
OBJECTIVE: A wide range in prevalence rates of burnout among general practitioners (GPs) has been reported in various regions, with an increasing trend. This nationwide cross-sectional study aimed to estimate the prevalence and associated determinants of burnout in Czech GPs. METHODS: 1000 randomly selected physicians from the Czech Society of General Practitioners (through a pseudorandom number generator) were emailed an online survey based on the Maslach Burnout Inventory - Human Services Survey. Data collection was performed between January and February 2023. RESULTS: 331 questionnaires were obtained (227 females and 104 males, mean age - 49.9 years, the mean number of registered patients - 1951). 21.8 % of GPs scored a high level of burnout in all three of its dimensions and 23.9 % in no dimension at all. The most prevalent dimension was reduced personal accomplishment (PA, 56.2 %) followed by emotional exhaustion (EE, 50.2 %) and depersonalization (DP, 40.5 %). Reaching burnout in all three dimensions was significantly more frequent in males and in GPs registering a number of patients above the median. Increasing age and years of practice were protective factors for DP but risk factors for reduced PA. Employed GPs had lower EE scores than GP practice owners. The respondents' basic characteristics reflected their presence among Czech GPs, which testifies against selection bias. CONCLUSIONS: The high rate of burnout (∼22 %) should be addressed by promoting personal resources along with the perception of the importance of GPs in society. A sufficiently dense network of GPs should allow them to register a lower number of patients.
Keywords: Depersonalization; Prevalence; Emotional exhaustion; Burnout; General practitioner; Job demands-resources model; Personal accomplishment